The Clearing - Ellis, JJJJJerome (Brooklyn : Wendy's Subway, 2023)
"The Clearing is a transcription of an album also called The Clearing, released by NNA Tapes (LP and digital) in collaboration with the Poetry Project. Each chapter corresponds to a track on the album, and each page corresponds to sixty seconds. The roman text corresponds to the spoken and sung "lyrics" of the album. The italic text is a description of the audio. My stutters-my clearings-are rendered in real time on the page. The "lyrics" began life as an essay, "The clearing: Music, dysfluency, Blackness, and time," published in 2020 in a special issue of the Journal of Interdisciplinary Voice Studies, edited by Daniel Martin and Maria Stuart"-- (Provided by publisher)
boek
Keywords: Ellis, JJJJJerome